The Role of Chickens in Vitamin Discoveries - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2006)
Animal models (bioassays) have been of great service to humanity in all sorts of scientific-related advancements. Aves, specifically chickens, played an important role in vitamin discoveries, as it was the first species to be used in 1890`s to study beriberi. We briefly review its 30-year trajectory as an investigational tool in science and medicine.